Digital practices of student citizenship: A case study of Chinese international students in Australia - Fu, Jun (Journal of International Students, 2025)
Research on international students’ academic experiences often emphasises the challenges of academic adjustment and the support that higher education institutions can provide. There is however limited research on the acquisition of social and emotional support, which is equally if not more important for their academic engagement, performance, and retention. Using the concept of digital citizenship, this paper explores how Chinese international students engage in mutual social and emotional support through performing their international student identities on Chinese social media platforms. These digital practices of student citizenship demonstrate the agency of international students in sourcing the social and emotional support that underpins their study. The paper further argues that research on international students should switch its focus from support provision to the construction of inclusive and equal social environments in host societies, environments in which different identity performances can be acknowledged and community engagement fostered.